Tradition of Mandoa Catampek and Ratik Tagak on Rayo Anam Day in Jorong Sikaladi Nagari Pariangan Flat Land District West Sumatra Province - Hasnah, Miftahul; septriani, Septriani (Kirana Publisher (KNPub), 2024)
This research was conducted in Jorong Sikaladi Nagari Pariangan, Tanah Datar Regency, West Sumatra Province. The aim of this research was to find out the background of the Mandoa Katampek and Ratik Tagak traditions and to describe the process of implementing the Mandoa Katampek and Ratik Tagak traditions on Rayo Anam Day. Tradition by Victor Turner. The method the author uses is a qualitative method, with data collection techniques namely observation, interviews and documentation. The results of the research show that the emergence of mandoa katampek and ratik tagak in Jorong Sikaladi Nagari Pariangan began around 400 years ago and was passed down to children nephews in each subsequent generation. The process of implementing this tradition can be grouped into three stages, namely the grave cleaning stage, the second stage of carrying out the tradition and the third stage of eating together,